3-D Printing: Its Applications in Pediatric Dental Practice: A Review of Literature (Indian Journal of Contemporary Dentistry, 2022)
Background: Over the last few years, Three-dimensional (3-D) printing, and prototyping has gained popularitywithin medical and dental profession and among patients alike. 3-D printing is an additive manufacturingtechnique in which objects are formed by deposition of material layer by layer. 3-D printers are machines thatproduce representations of objects either planned with a CAD program or scanned with a 3-D scanner. Thisarticle highlights the evolution, benefits and application of 3-D printers in pediatric dentistry.
Keywords: Additive Manufacturing, 3-D printers, Pediatric Dentistry, customization, digital dentistry